IMPLEMENTASI PERPUSTAKAAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH PADA BERBAGAI JENJANG SEKOLAH DI KOTA PADANG - Qowaid Qowaid (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Library and education are two related concepts. Both can be functional in increasing the quality and prosperity of the people. This is also with inserting Islamic education in schools. Considering upon the existence of Islamic education in schools, the Indonesian ministry of religious affairs has established the ordinance Number 211 Year 2011 concerning the standard of an Islamic educational library in schools. The idea of this research isconducted by the existence of the ordinance which shall be focused on acknowledgement, implementation, and alternative implementation in schools. The result of this research indicates that the law which is related to the standard of the facility and utility of the Islamic educational library for schools are yet still not known by many. Every school by the research has not yet possesses an Islamic educational library and mentioned as it is. The implementation experiences difficulties such as financial support, space, and human resources. The alternative suggested by the research; first: to construct buildings/rooms for the Islamic educational libraries; second: the library must become a part from the general library in school; third: the library may use spare rooms from the school’s mosques or mushallas.